ENHANCING STUDENTS' UNDERSTANDING OF RAMADAN FASTING THROUGH A DIGITAL INTERACTIVE WEBSITE: A STUDY IN ISLAMIC SECONDARY EDUCATION - Anam, Choirul; Nurhidayah, Rahmawati Eka; Wibowo, Asrizal Septi; Nugroho, Alan Alda (POTENSIA: Jurnal Kependidikan Islam, 2025)
The conventional teaching methods in Islamic Education (PAI), particularly on the topic of Ramadan fasting, often fail to engage students effectively. To address this issue, this study aimed to develop and evaluate the effectiveness of a web-based interactive learning platform for teaching Ramadan fasting to secondary school students at MTs Ma'arif 01 Tulakan. Using the ADDIE model, the research followed a systematic process: analysis, design, development, implementation, and evaluation. The platform incorporated features such as quizzes, educational videos, and discussion forums to create an engaging and accessible learning experience. A pre-test and post-test experimental design involving 20 students revealed a significant improvement in comprehension, with mean scores increasing from 61.00 to 82.50 (t = -9.731, p < 0.000). Additionally, feedback from students highlighted high satisfaction levels regarding ease of access (88%), usability (85%), and content quality (86%). The findings demonstrate the platform’s potential to enhance students’ understanding and engagement in Islamic education through digital innovation. This study provides a replicable model for integrating technology into Islamic educational practices, offering a pathway for further advancements in digital learning environments.